ENZIM MANANASE DAN FERMENTASI JAMUR UNTUK MENINGKATKAN KANDUNGAN NUTRISI BUNGKIL INTI SAWIT PADA PAKAN IKAN NILA BEST (Oreochromis niloticus) - Bakara, Okta; Santoso, Limin; Heptarina, Deisi (AQUASAINS, 2013)
Palm kernel meal is CPO (CrudePalm Oil)-by product are potentially asan alternative raw material fish feed. Thisresearch aims to know the influence of theenzyme mananase and mold fermentationto improve the quality of palm kernel overthe extent of the digestibility of oreochromisBEST. This study used a RandomizedComplete design of experiment method(RAL) with seven treatments and three replicateseach. BEST tilapia with weights 25Â± 1.57 gram put in 21 60x40x40cm3 sizedaquarium. Test feed was given for 15 daysas a mortgage with a frequency three timesa day. The results showed that the total digestibility(56,74%) and protein digestibility(82,38%) resulting from the best treatmentof palm kernel with the addition ofmananase enzyme and fermentation of themold Rhizopus oligosporus and for carbohydratedigestibility (60,72%) and energydigestibility (71,82%) obtained the best resultfrom the treatment of palm kernel withthe addition of mananase enzyme and fermentationof Trichoderma reesei mould.